2020
DOI: 10.3390/min10111015
|View full text |Cite
|
Sign up to set email alerts
|

Editorial for Special Issue “Sustainable Use of Abandoned Mines”

Abstract: Abandoned mines are an abundant and widespread feature [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, global markets dictate the viability of mines, with many mines closing for extended periods or even being abandoned as the cost of extraction exceeds market prices. As recent research has noted, abandoned or former mine sites are a common feature around the world, with Gutierrez (2020) estimating there to be approximately 500,000 such sites in the United States, 50,000 in Australia, and 10,000 in Canada. Werner et al (2020) identified 95,320 mine sites, including shafts, in Australia, of which some 89% were inactive.…”
Section: Planning For a Post‐mine Futurementioning
confidence: 99%
“…Furthermore, global markets dictate the viability of mines, with many mines closing for extended periods or even being abandoned as the cost of extraction exceeds market prices. As recent research has noted, abandoned or former mine sites are a common feature around the world, with Gutierrez (2020) estimating there to be approximately 500,000 such sites in the United States, 50,000 in Australia, and 10,000 in Canada. Werner et al (2020) identified 95,320 mine sites, including shafts, in Australia, of which some 89% were inactive.…”
Section: Planning For a Post‐mine Futurementioning
confidence: 99%
“…Recently, the pollutants was consist the metals, petroleum, and organic hydrocarbons although the compounds for pesticides and herbicides. Certain techniques in bioremediation were shown in table 1 [6][7][8][9].…”
Section: Bioremediation Of the Ex-mining Landmentioning
confidence: 99%